Land Bank as Land Provision Agency in Land Procurement for Public Interest - Trischa Galuh Krishnasanti; Made Widya Prasasti (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2023)
The idea of creating regulations about Land Bank is getting stronger by seeing many problems regarding the land supply for development for the public interest. The enactment of Law Number 11 of 2020 concerning Job Creation is the basis for the establishment of the Land Bank Agency. The mandate of Article 33 paragraph (3) of the 1945 Constitution and Article 2 of Law Number 5 of 1960 concerning Basic Agrarian Principles says that the State has the authority to control, regulate, and organize the allotment of land, water, and natural resources contained therein for the people greatest prosperity. However, the availability of land amount is not proportional to the massive development by people and the government conduce in land price fluctuations. Moreover, the absence of a land operator role hinders infrastructure development for the public interest. The purpose of this study is to reveal the legitimacy of the Land Bank Agency in land procurement for development in the public interest after the enactment of Omnibus Law and to describe land acquisition by the Land Bank Agency. The doctrinal research method is used in this study. Approach methods that are used in this study are the statute and conceptual approaches. It was found that the legitimacy of the Land Bank Agency is a form of the authority of the State Right to Control over Land which carries out functions as a land manager and guarantees the availability of land in for the public interest so that the Land Bank Agency can act as an agency that requires land in land acquisition for development for the public interest. The acquisition of land by Land Bank Agency is carried out through government determinations and through a waiver of rights.